2010
DOI: 10.1097/ypg.0b013e32833adccb
|View full text |Cite
|
Sign up to set email alerts
|

The dopamine D2 receptor gene and depressive and anxious symptoms in childhood: associations and evidence for gene–environment correlation and gene–environment interaction

Abstract: Objectives Research implicates the A1 allele of the dopamine D2 receptor gene (DRD2) Taq1A polymorphism in the development of depression and anxiety. Furthermore, recent papers suggest that children with A1 allele of this gene may receive less positive parenting, and that the effects of this gene on child symptoms may be moderated by parenting. We sought to replicate and extend these findings using behavioral measures in a nonclinical sample of young children. Methods In a sample of 473 preschool-aged childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 39 publications
4
71
1
1
Order By: Relevance
“…Consequently, our results should not be interpreted as implying a direct link between Taq1A and depression, either in smokers or nonsmokers. To date, evidence for such a link appears to be confined to the childhood development of anxiety and depression [36]. As we had no specific hypothesis about the form of the association between Taq1A, depression and smoking cessation, our results must be regarded with caution.…”
Section: Discussionmentioning
confidence: 67%
“…Consequently, our results should not be interpreted as implying a direct link between Taq1A and depression, either in smokers or nonsmokers. To date, evidence for such a link appears to be confined to the childhood development of anxiety and depression [36]. As we had no specific hypothesis about the form of the association between Taq1A, depression and smoking cessation, our results must be regarded with caution.…”
Section: Discussionmentioning
confidence: 67%
“…This possibility is further supported by other evidence suggesting that child temperamental negative emotionality may elicit more negative parenting, but only if the parent experienced negative parenting behaviors in their childhood (Scaramella & Conger, 2003). Given that negative emotionality is associated with having a short allele on 5-HTTLPR (Hayden et al, 2010; Pauli-Pott et al, 2009), this further supports the possibility that children’s genotype may influence parenting behaviors, but only if the parents experienced lower quality parenting themselves.…”
Section: Cross-generational Transmission Of Parenting and Gene-enviromentioning
confidence: 66%
“…This possibility would be consistent with the growing rGE literature, although most studies have used quantitative genetic, rather than measured gene, approaches (see Kendler & Baker, 2007; Avinun & Knafo, 2014, for meta-analyses). However, a handful of studies examined variations of children’s dopaminergic genes and found associations with negative parenting (Hayden et al, 2010; Hayden et al, 2013; Lucht et al, 2006; Mills-Koonce et al, 2007), and one study found associations with oxytonergic genes (Kryski et al, 2014). Other research has found associations between child catechol-O-methyltransferase genotype and positive parenting (Oppenheimer et al, 2013).…”
Section: Cross-generational Transmission Of Parenting and Gene-enviromentioning
confidence: 99%
“…Indeed, a potentially complementary line of research implicates DRD2 in gene-environment correlations and interactions, in addition to its influence on the way in which symptoms present. 43 Nevertheless, one strength is that this was the first study to examine both the demographic/clinical and genetic correlates of primary symmetry symptomatology in OCD.…”
Section: Discussionmentioning
confidence: 99%